Heterogeneous rental markets in a DSGE model of the euro area - Patrick Hirsch (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The euro area economies are bound together by monetary policy while still inhibiting many heterogeneities. Amongst them the share of homeowners. This paper presents a medium scale New Keynesian DSGE model of the euro area with an extensive housing market which explicitly models endogenous tenure choice. Results from the calibrated model indicate that there are various parameters determining the ownership rate. Dependent on the drivers of the homeownership, shocks have substantial heterogeneous effects on real variables when rates differ across countries.
Keywords: E32; 330; DSGE; ownership-rates; housing; heterogeneities; monetary union